Technical vocational livelihood series: housekeeping - Vivas, Jennifer F. (Quezon City : Phoenix Publishing House, Inc., 2016)
"Housekeeping is one of the courses in Technical Vocational Livelihood (TVL) Track for grade 11 that helps learners obtain National Certificate (NC) II from the Technical Education and Skills Development Authority (TESDA). This book covers five core competencies that learning need to have as prescribed by the Tesda Training Regulations; providing housekeeping services ; preparing rooms for guest; cleaning premises; providing valet/butler services; and launder linen and guest clothes. Each lesson in this book has varied and relevant assessment activities. Indoor and outdoor activities in the lessons prepare and expose learners to the work industry. "
English text.
Keywords: Housekeeping management